The Effectiveness Of Instagram Social Media In Building The Branding Of Nonformal Educational Institutions (A Study Of Razaka Academy Jambi) - Ridho Agung Prayogi; David Iqroni; Mohd. Adrizal (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
One platform that stands out in this phenomenon is Instagram. This research aims to provide an empirical description of the effectiveness of Instagram as a branding tool for non-formal educational institutions and to serve as a basis for developing a more focused and data-driven digital branding strategy. This study employed a quantitative approach using an explanatory survey method. The sampling technique applied was purposive sampling, and the research instrument used was a questionnaire distributed to Instagram followers of Razaka Academy. The findings indicate that the effectiveness of Razaka Academy's Instagram social media is categorized as high, with an average score of 87.74 out of 100. Furthermore, branding perception based on followers’ responses is also in the high category, with an average score of 70.44 out of 80. The results of the simple linear regression analysis reveal that Instagram effectiveness has a positive and significant effect on Razaka Academy's branding. The correlation coefficient (R) of 0.928 indicates a very strong relationship. The coefficient of determination (R²) of 0.861 shows that 86.1% of branding variation is explained by Instagram effectiveness, while 13.9% is influenced by other factors.